Complications of Measles in Malnourished Children, a Descriptive Cross-Sectional Study at a Tertiary Care Hospital Rawalpindi - Rai Muhammad Asghar, Muddassar Sharif, Isfand Yar Khan, Abid Hussain Syed, Rai Rijjal Ashraf, Muhammad Hussain, (Journal of Rawalpindi Medical College, 2022)
Objective: To determine the frequency of common complications of measles in malnourished children. Materials and Methods: This study was conducted in the Department of Pediatrics Benazir Bhutto Hospital, Rawalpindi from January 2018 to December 2018. Through a Descriptive Cross-Sectional Study Design, a total of 110 cases of measles with malnutrition presenting to the Paediatrics Department were selected and observations were recorded on follow up. Results: The mean age was 2.7 years (SD±1.2) of which 61% (n=67) were male and 39% (n =43) were female patients. 35.5% (n=39) presented with grade I, 24.5% (n=27) in grade II and 40% (n= 44) in grade III malnutrition. On follow up, pneumonia was observed in 39.1%, diarrhea in 36.4%, otitis media in 10% and encephalitis in 8.1% of children. The most frequent complications were observed in grade II and grade III malnourished children and children of younger age groups. Conclusion: Measles and malnutrition are still calamity in our population as once together, the complications of each other are more prevalent and preventive projects must be designed with full efficacy against both these conditions.